2021
DOI: 10.1016/j.jtocrr.2021.100239
|View full text |Cite
|
Sign up to set email alerts
|

MET Amplification and Efficacy of Nivolumab in Patients With NSCLC

Abstract: Introduction MET amplification is an important genetic alteration in NSCLC. Unlike in patients with EGFR and ALK alterations, the efficacy of immune checkpoint inhibitors in patients with MET -amplified NSCLC remains unknown. Methods An exploratory analysis of a prospective, multi-institutional cohort comprising 200 patients with advanced or recurrent NSCLC treated with nivol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“… 24 A subgroup analysis of the PROFILE 1001 study showed that the ORR in the high MET amplification group (MET/CEP7 ≥ 4.0) was 38.1% with a median PFS of 6.7 months, which was significantly higher than that of the medium or low MET amplification group. 25 In our study, the correlation between MET amplification GCN and prognosis likewise existed. High MET amplification GCN was associated with better MET TKI efficacy.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“… 24 A subgroup analysis of the PROFILE 1001 study showed that the ORR in the high MET amplification group (MET/CEP7 ≥ 4.0) was 38.1% with a median PFS of 6.7 months, which was significantly higher than that of the medium or low MET amplification group. 25 In our study, the correlation between MET amplification GCN and prognosis likewise existed. High MET amplification GCN was associated with better MET TKI efficacy.…”
Section: Discussionsupporting
confidence: 61%
“…Studies have shown that high MET amplification is associated with strong oncogenic driving character 24 . A subgroup analysis of the PROFILE 1001 study showed that the ORR in the high MET amplification group (MET/CEP7 ≥ 4.0) was 38.1% with a median PFS of 6.7 months, which was significantly higher than that of the medium or low MET amplification group 25 . In our study, the correlation between MET amplification GCN and prognosis likewise existed.…”
Section: Discussionsupporting
confidence: 60%
“…The ORR in patients with high and intermediate numbers of MET gene copies (50.0% for both) was significantly higher than those without increased MET gene copy number (17.6%), yet survival outcomes for both PFS and OS did not improve. This study showed that an increase in the MET gene copy number was not associated with greater efficacy of nivolumab in patients with NSCLC [22].…”
Section: Discussionmentioning
confidence: 59%
“…A total of 29 publications providing information on disease characteristics of MET amp NSCLC were identified ( 23 51 ). A summary of results from 16 US- or non-US based studies that evaluated demographic and clinical characteristics of patients with NSCLC with or without MET amp is found in Supplementary Table 4 ( 24 27 , 29 , 32 , 33 , 35 37 , 44 47 , 50 , 51 ).…”
Section: Resultsmentioning
confidence: 99%